URGENSI IMPLEMENTASI PEMBELAJARAN PKN DALAM PENANAMAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Eka Ridha Nofrida; Bherrio Dwi Saputra (Universitas Sarjanawiyata Tamansiswa, 2022)
Abstract: This article describes how the implementation of Citizenship Education learning in the cultivation of character education in elementary schools with the method used is literature review. There are 5 discussions in this article, namely the implementation of Civics learning in elementary schools, planting character education through Civics learning, how to instill character education strategies, obstacles, and expectations for implementing character education. The results obtained are that character education in elementary schools is a good step taken so that the Indonesian nation avoids a moral crisis, one way to instill character education is through Civics lessons, there are 7 strategies in character building, although character education faces obstacles in its implementation but there are ways to handle it, and hope that the quality of education and Indonesian students will improve from time to time.